ANALYSIS OF THE RELATIONSHIP OF TRAINING EDUCATION AND WORK MOTIVATION WITH PERFORMANCE OF EMPLOYEES IN THE DEPARTMENT OF POPULATION AND CIVIL REGISTRATION IN THE CITY OF SURAKARTA - R.Aj Gayatri Koes Maharani; Herbasuki Nurcahyanto; Aufarul Marom (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2021)
The purpose of the study was to analyze relationship between education and training (training) with employee performance and work motivation with the performance of the Surakarta City Population and Civil Registration Office. This research is an explanatory research using quantitative methods. The respondents were 29 employees of the Surakarta City Population and Civil Registry Office. The result of this research is the correlation coefficient value of education and training on employee performance using Kendall Tau is 0.438 with a coefficient of determination of 19.18%. The correlation coefficient value of work motivation on employee performance using Kendall Tau is 0.634 with a coefficient of determination of 40.19%. The concordance coefficient of training and work motivation on employee performance is 0.65 sig (0.000) <(0.01). The coefficient of determination of training and work motivation on employee performance is 42.25%. The conclusion of this study is that there is a positive influence and a very significant relationship between training and work motivation on the performance of the Surakarta City Population and Civil Registry employees.